The Integration of Artificial Intelligence and Public Relations:An Analytical Study of AI Use in Communication Messages to the Public - Aqeel Tahseen Fathallah; Ali Muhanad Hamid; Osama Kareem Rasheed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
The goal of this study is to identify the various uses of Artificial intelligence (AI) applications in shaping the communication messages directed to the public and how the audience interacts with these messages. It further explores the extent to which AI contributes to influence and persuasion within the framework of public relations message design, based on this, the study focuses on the following central question: “What is the role of artificial intelligence in generating public communication messages?” The researchers adopted the descriptive approach, which is a type of research methodology aimed at explaining and accurately describing the phenomenon in light of the study variables.The findings reveal that the research sample used AI applications partially to produce communication messages to the target audience with a frequency of (833) representing (69%), Additionally, the results indicate that video-based reports incorporating AI-generated narration and imagery ranked first among content formats, with a frequency of 800 (66.6%) of the total sample.DOI: https://doi.org/10.54633/2333-025-058-014